Amnesties in Strasbourg - Jackson, M (Oxford University Press, 2018)
This article concerns the permissibility of amnesties under the ECHR. It argues that when an amnesty case comes to Strasbourg, as it probably will, there is a good chance that the Court will make a serious error. That error will be to hold that the Convention requires the prosecution of the gravest human rights abuses in all circumstances – it will be to invalidate the amnesty. In part, such an approach will likely be informed by an assumption that each of the duties that flows from an absolute right is itself absolute. That assumption, combined with the way that the Court has specified the prosecutorial duty, would prevent the Court from taking into account powerful countervailing interests in play during peace negotiations. These countervailing interests mean that a claim that amnesties for the gravest wrongs are always impermissible is unsustainable.